Implementation of Digitalized Economy in Developing E-Commerce-Based Ornamental Plant Cultivation Business on Madirsan Street in Bangun Sari Village, Tanjung Morawa District - Cut Sah Kha Mei Zsazsa; Boby Indra Prayoga (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study examines the limited application of the digital economy in developing e-commerce-based ornamental plant cultivation businesses in Bangun Sari Village, Tanjung Morawa District. The problem emerges from the fact that many ornamental plant traders along Jalan Madirsan still depend on conventional marketing, especially direct selling, while only a few have begun using social media platforms such as Facebook. Most traders are older community members who have limited digital literacy and have not fully utilized e-commerce to expand market access, strengthen promotion, and improve business competitiveness. In this context, the village government has an important role in encouraging digital transformation through training, assistance, and collaboration with local business actors. Bangun Sari Village has strong economic and environmental potential because ornamental plant cultivation is practiced by many residents, creating an attractive, beautiful, and cool village landscape. This potential can become a distinctive village asset if supported by broader digital promotion. This research uses a descriptive qualitative method, with informants consisting of ornamental plant traders on Jalan Madirsan. Data were collected through literature study, observation, and interviews. The findings indicate that the implementation of digital economic practices in e-commerce-based ornamental plant business development remains suboptimal and requires stronger institutional support and guidance